Consistency of uroflowmetry analysis in children among observers. Issue 3 (7th February 2023) - Sekerci, Cagri Akin; Tanidir, Yiloren; Tarcan, Tufan; Yucel, Selcuk
Abstract: Aim: The aim of the study is to compare the intra‐ and inter‐observer interpretations of the same uroflowmetry study at two different times. Materials and Methods: Two‐hundred children with a voided volume of 50% above the expected bladder capacity were included. All traces were asked to be evaluated by 11 observers two times in a time span of 1 month. These observers consist of pediatric urologists ( n = 2), pediatric urology fellows ( n = 2), urology residents ( n = 5), and certified urodynamics nurses ( n = 2). Each uroflowmetry was asked to be assessed for three domains: voided volume (VV), detrusor sphincter dyssynergia (DSD), and flow curve pattern (FCP). Results: Of the 200 patients with a median age of 10 (4–18) years, 128 (64%) were girls and 72 (36%) boys. The maximum flow rate and the median voided volume were found to be 20 (4–61) mL/s and 232 (116–781) mL. The Fleiss' kappa coefficient of VV, DSD, and FCP in the first assessment was 0.510, 0.501, and 0.346. In the second assessment, κ values were 0.530, 0.422, and 0.373. The best‐agreed findings were similar at both times. These were found to be low VV (0.602 and 0.626) and intermittent pattern (0.500 and 0.553). Interpreters were found to have a statistically significant difference in agreement with their own interpretation at different times. Conclusion: Both inter‐ and intra‐observer reliability of the agreement point out the problem in the standardization of uroflowmetry. Inter‐ and intra‐observer reliability of uroflowmetry interpretation can be increased by defining precise numbers and numerical algorithms.